2019
DOI: 10.1002/14651858.cd009487.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pararectal versus transrectal stoma placement for prevention of parastomal herniation

Abstract: Lateral pararectal versus transrectal stoma placement for prevention of parastomal herniation (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The literature review identified that preoperative marking for ideal stoma site placement by qualified personnel reduces the risk of early complications and leads to higher health-related quality of life and should be mandatory in elective cases. 7 , 8 , 10 , 11 , 16 – 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review identified that preoperative marking for ideal stoma site placement by qualified personnel reduces the risk of early complications and leads to higher health-related quality of life and should be mandatory in elective cases. 7 , 8 , 10 , 11 , 16 – 23 …”
Section: Resultsmentioning
confidence: 99%
“… 5 A recent Cochrane review identified that insufficient evidence existed to recommend either lateral pararectal or transrectal placement of stomas. 23 …”
Section: Resultsmentioning
confidence: 99%
“… failed to demonstrate any relationship with PSH formation. Similarly, a Cochrane review from 2013 also failed to demonstrate any association between stoma position in relation to the rectus sheath and PSH formation .…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 3500 stomas are created annually [ 3 ] and approximately 35,000 persons live with a stoma in Sweden [ 4 ]. Symptoms of PSH include cosmetic disfiguration and impaired body image, stoma dressing problems leading to leakage and skin irritation, prolapse and life-threatening intestinal incarceration [ 5 ]. Indications for surgical treatment commonly include pain, dressing problems, intestinal obstruction or strangulation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%